2018
DOI: 10.3892/mmr.2018.9252
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑665 suppresses the growth and migration of ovarian cancer cells by targeting HOXA10

Abstract: Ovarian cancer is the most lethal gynecological cancer and its metastasis leads to a poor prognosis. The present study was designed to elucidate how microRNA (miR)-665 regulates the proliferation and migration of ovarian tumor cells. Reverse transcription-polymerase chain reaction (RT-PCR) demonstrated that miR-665 expression was decreased in ovarian cancer tissues. Increased expression of miR-665 suppressed the growth and migration of ovarian cancer cells, whereas the downregulated expression of miR-665 led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Western blot analysis was conducted to examine the expression levels of p-β-catenin, β-catenin, and cyclin D1. ovarian cancer 29 and pancreatic cancer. 36 However, the expression profile of miR-665 in RB had not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blot analysis was conducted to examine the expression levels of p-β-catenin, β-catenin, and cyclin D1. ovarian cancer 29 and pancreatic cancer. 36 However, the expression profile of miR-665 in RB had not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…27 In contrast, miR-665 plays an inhibitory role in the growth and invasion of ovarian cancer cells. 29 A study by Dong et al revealed that upregulation of miR-665 expression attenuated the proliferation, invasion, and epithelial-mesenchymal transition of osteosarcoma cells. 28 However, the functional roles of miR-665 in RB cells have remained largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, tumor cell migration and invasion are enhanced by the overexpression of miR-665 by promoting the epithelial-mesenchymal transition process (34). By contrast, miR-665 has been demonstrated to suppress cell proliferation and migration in ovarian cancer cells (35). This controversy on the role of miR-665 may be due to the different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA‐665 was downregulated in ovarian cancer, pancreatic cancer, hepatocellular carcinoma, inflammatory bowel disease, and so on. However, the role and mechanism of miR‐665 in CC remains unknown.…”
Section: Discussionmentioning
confidence: 99%